Stability of non-localized responses for damaging materials - Pham, K.; Marigo, J. J. (Vietnam Journal of Mechanics, 2008)
This work is devoted to the analysis of the stability of the homogeneous states of a bar made of a brittle strain softening material submitted to a tensile loading. We distinguish two types of damage models: local damage models and gradient damage models. We show that a local damage model necessarily leads to the unstability of the homogeneous response once the first damage threshold is reached. On the contrary, in the case of a gradient damage model, viewed as a regularization of the underlying local model, the homogeneous damage states of “sufficiently small" bars are stable